Istano Basa Pagaruyung: The Functional Values of the Building Toward its Residents, The Social Community, and Educational Elements - Yumielda , Vivi Destri; Efi, Agusti (Universitas Jambi, Indonesia, 2023)
Istano Basa Pagaruyung has a function from a Minangkabau perspective. . As a Minangkabau heir, it is obliged to study the culture and function of this perspective, especially for students. However, as time went by, there were changes in the social culture of the Minangkabau people, who started to abandon the Rumah Gadang architectural style, so it influenced the knowledge of the Minangkabau people themselves regarding cultural values, especially the construction of Istano Basa Pagaruyung as a Minangkabau cultural heritage. It is due to socio-cultural changes in society.